RUSSIA’S EFFORT IN GETTING CRIMEA BACK - Galuh Pramita Ayu (2016)
Conflict in Crimea was once a focus of international sphere in 2014. The conflict was triggered by the tendency of Ukraine to join European Union. Crimea, a peninsula located in southern, was one of the regions that prefer Ukraine join Russian Federation to European Union. Crimea has Russian-speakers as the majority population in this area. They did protest and demonstrations in the end of 2013 until early 2014. The protests were not responded very well. Ukrainian parliament simply accused them as separatist movement. This paper will analyze the causes of the conflict and the effort of Russia to get the Crimea back. However, we have to understand first that there are three major factors that might be the cause of the conflict. Gurr (2001) stated that those three factors are local, national, and international contexts. Thus, this journal will analyze more on the international context.